Estrés laboral y la productividad de las personas con discapacidad: antesala literaria - Gallegos Erazo, Franklin (2018)
For a long time people with disabilities have been left aside, the percentage of people represented by a sample of the population and many others linked to the business sector. Studies carried out by institutions worldwide indicate that the possible causes of the difficulty of inserting people with disabilities in the labor market depend on the great magnitude of the level of education, the lack of motivation in the environment, the negative initiative and the difficulties in accessing or moving to their places of work. This article summarizes the reasons why a job is assigned to the PCD, the effects of disability on stress, salary differences and the performance of people in the labor market.